PENGEMBANGAN BUKU CERITA BERGAMBAR SEBAGAI MEDIA PEMBELAJARAN TEMATIK TEMA HIDUP BERSIH DAN SEHAT KELAS II SDIT SYIFAURRAHMAH KECAMATAN PATUMBAK - Indah Ansari (PGSD UMN Al-Washliyah, 2022)
This development research aims to develop a picture story book as a thematic learning media on the theme of clean and healthy living that is suitable for use for learning. This research is a type of research and development using the Borg and Gall development model. The researcher carried out the Borg and Gall development model to the product revision stage. The instrument used to collect data is a questionnaire or questionnaire given to validators, namely media expert validators, material expert validators and learning expert validators. Based on the validation results from media expert validators, an average score of 3.71 was obtained in the